2011
DOI: 10.1111/j.1610-0387.2011.07710.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of baby swimming and baby lotion on the skin barrier of infants aged 3-6 months

Abstract: Reaction of skin barrier function to baby swimming and skin care regimens showed typical regional variability between body areas. Influence of baby lotion on skin barrier and gender differences in skin functional parameters were demonstrated for the first time in healthy infants participating in baby swimming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 18 publications
5
22
0
1
Order By: Relevance
“…Furthermore, the present study demonstrated similar or higher SCH values than those of full-term and young infants, as found in recent studies with matching methods and measurement locations [10,24]. This finding could be attributed to the effect of adequate incubator therapy on preterm infants [13].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Furthermore, the present study demonstrated similar or higher SCH values than those of full-term and young infants, as found in recent studies with matching methods and measurement locations [10,24]. This finding could be attributed to the effect of adequate incubator therapy on preterm infants [13].…”
Section: Discussionsupporting
confidence: 73%
“…Skin pH on the forehead, abdomen and leg exhibited a decrease after birth during the entire study period, reaching values comparable to those reported in 2- to 6-month-old infants [24,26,28]. This decrease suggests an adaptation process of the epidermal barrier with formation of the acid mantle on non-diapered areas during the first weeks of life [10].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In order to scientifically characterize the effect of the emollients applied, we assessed the functional skin parameters SCH, TEWL and pH by established, noninvasive methods in three representative areas of investigation [39]. The previously reported anatomical variability in infant skin has to be considered when evaluating the effect of regular emollient application on skin barrier function [14,16,17,38,40,41]. Skin lesions in AD are characteristically distributed in an age-related pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, current awareness of dry skin condition and effective treatment of children with atopic predisposition is limited [36,37]. Regular application of emollients is discussed to exert a positive effect on skin barrier function in infants [17,38]. In order to scientifically characterize the effect of the emollients applied, we assessed the functional skin parameters SCH, TEWL and pH by established, noninvasive methods in three representative areas of investigation [39].…”
Section: Discussionmentioning
confidence: 99%